1, 8-Diazabicyclo[5.4.0]undec-7-ene (DBU)-promoted reduction of azides to amines under metal-free conditions. (20th May 2022) - Xu, Shijie; Yang, Fan; Fan, Hui; Zhao, Xuechun; Xu, Yao; Wang, Shuo; Zhang, Xiaoxiang
Abstract : A simple and novel metal-free reduction of azides to amines in the presence of DBU is reported. This DBU-promoted transformation features good functional group tolerance and high chemo-selectivity. Abstract : A simple and novel metal-free reduction of azides to amines in the presence of DBU is reported. Aromatic and sulfonyl azides are typically used to give the desired amines in moderate to excellent yields. This transformation features good functional group tolerance and high chemo-selectivity. In this reduction, functional groups such as alkynes, halides, ethers, esters and cyano groups are not affected. DBU is used as not only the solvent but also the reducing reagent.